Collectivism versus individualism: performance-related pay and union coverage for non-standard workers in Britain - Alison L. Booth; Marco Francesconi (University of Essex, Institute for Social and Economic Research (ISER), 2000)
This paper documents the extent of union coverage and performance-related pay (PRP) the latter representing one aspect of pay flexibility across standard and non-standard workers in Britain, using the first seven waves of the British Household Panel Survey, 1991-1997. We find there is no evidence of expansion of either union coverage or PRP towards any type of non-standard employment in the 1990s. Thus union rhetoric about a strategy of enlargement towards non-standard workers remains just that. The only trend over time that we do observe is a continued small decline in union coverage for all male workers (but not for women) and a continued very small growth in PRP coverage for all women (but not for men). In addition, while we find large gender differences in union coverage across non-standard workers, there are only negligible gender differences in PRP incidence. Moreover, the relationship between non-standard employment and PRP is typically weak for both men and women. We also find significant occupational and sectoral differences in union coverage and PRP incidence across non-standard workers.
Keywords: 330